Young patients with cancer and a digital social network: the voice beyond the clinic - Elisa Fontana; Florian Lordick; Irit Ben-Aharon; Tal Goshen-Lago; Ilit Turgeman; Elizabeth Smyth (ESMO Open, 2020)
Introduction Digital social networks have become a key player in the ecosystem of young patients with cancer, with regard to their unique perspectives and unmet needs. This study aims to investigate the web-based social community tools and to characterise the user profile, unmet needs and goals of young patients with cancer.Methods A web-based survey was distributed via large-scale social network designated for young patients with cancer (age 18–45 years) Stop Cancer. The survey collected demographic data and oncological status. Primary outcome was potential goals of accessing the network; secondary outcomes were emotional impact, effect of disease status, education, marital status and employment, on user satisfaction rate.Results The survey was available for 5 days (10/2018) and was filled by 523 participants. Breast cancer, haematological malignancies and colorectal cancer were the most common diagnoses. The majority had non-metastatic disease at diagnosis, 79% had no evidence of disease at time of the survey. Forty-five per cent considered the network as a reliable source for medical information. Academic education was associated with higher satisfaction from the platform. There were no differences between cancer survivors and patients with active disease in patterns of platform usage. The social network had an allocated section for ‘patient mentoring’ of newly diagnosed members by survivors.Discussion Our study portrayed the user prototype of a social digital network among young adult patients with cancer, indicating challenging trends. Whereas social media may prove a powerful tool for patients and physicians alike, it may also serve as a research tool to appraise wide practices within a heterogeneous population. Nevertheless, it acts as a double-edged sword in the setting of uncontrolled medical information. It is our role as healthcare providers to join this race and play an active role in shaping its medical perspectives.